Effect of 12-Week Aerobic Exercise Training on Chemokine Ligands and Their Relative Receptors in Balb/C Mice with Breast Cancer - Esmailiyan, Mehrnoosh; Nobari, Hadi; Kargarfard, Mehdi; Amerizadeh, Atefeh; Esfarjani, Fahimeh; Vaseghi, Golnaz; Badicu, Georgian; González, Pablo Prieto; Ardigo, Luca Paolo (International Journal of Sport Studies for Health, 2023)
Background: Some chemokines like C C motif chemokine ligand (CCL) 2 and 5 and their receptors (CCR) 2 and 5 are mediators of chronic inflammation and cancer development. Moreover, physical exercise can increase the activity of antioxidant enzymes. However, its effect on cancer cells has not been reported at present.Objectives: Therefore, the present study aimed to ascertain the effect of 12-week aerobic exercise training (AET) on CCL2, CCR2, CCL5, and CCR5 in mice with breast cancer.Methods: Sixteen Balb/c mice aged 4 - 5 weeks (n = 16; approximate weight: 18 ± 2 g) were divided into two groups: AET group (AETG) and control group (CG) (n = 8 per group). The AETG performed 12-week treadmill running at 18 m/min for 40 min and five times a week. Plasma levels of CCL2 and CCL5 were measured by ELISA, and the CCR2 and CCR5 were evaluated by Western blotting. Two independent sample t-test was applied to compare the differences between AETG and CG.Results: The analysis displayed after 12 weeks showed a significant reduction in AETG compared to CG in CCL2 (3.94 ± 1.12 vs. 15.40 ± 3.29 pg/mL; P = 0.001), CCR2 (0.56 ± 0.19 vs. 1.00 ± 0.001; P = 0.002), CCL5 (138.59 ± 15.72 vs. 267.57 ± 49.06 ng/mL; P = 0.001) and CCR5 (0.36 ± 0.12 vs. 1.00 ± 0.001; P = 0.001), respectively.Conclusions: We concluded that one of the main mechanisms of a positive effect of exercise on breast cancer is reducing the inflammation via CCL2 and CCL5 and their related receptors CCR2 and CCR5, respectively. Since these molecules can be triggered off oxidative stress and tumorigenesis, these results can pave the way for further studies in this field.